Power Efficient Resource Allocation of OFDMA Wireless Network - S. Saravana Kumar, S.; Umapathy, K. (International Journal of Engineering and Technology, 2018)
Multihop cellular network have drawn great attention for the future generation cellular network because of it through put and coverage. But still there are few problems facing by MCNâ€™s are interference and frequency resources which leads to traffic congestion and lack in QOS. Thus paper introduces the heuristic algorithm which provides a good Quality of Service (QoS) and reduced interference compared to the existing techniques. Power allocation of cell-edge users is optimized through radio resources. Simulation result shows the throughput achieved for cell-edge and cell-centre users using power allocation.Â Â